2000
DOI: 10.1002/1097-0231(20000915)14:17<1619::aid-rcm71>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput cytochrome P450 (CYP) inhibition screening via cassette probe-dosing strategy. I. Development of direct injection/on-line guard cartridge extraction/tandem mass spectrometry for the simultaneous detection of CYP probe substrates and their metabolites

Abstract: A highly efficient direct injection/on‐line guard cartridge extraction/tandem mass spectrometry (DI‐GCE/MS/MS) method utilizing electrospray polarity switching was developed for the simultaneous detection of probe substrates and marker metabolites of seven human hepatic cytochrome P450 (CYP) isozymes: CYP1A2, 2A6, 3A4, 2C9, 2C19, 2D6 and 2E1. Microsomal incubations were terminated with formic acid, centrifuged, and the resulting supernatants were injected for analysis by DI‐GCE/MS/MS. This method employed an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 12 publications
1
34
0
Order By: Relevance
“…Currently, the most widely employed incubation sample preparation is protein precipitation (PPT) [11][12][13][14][15][16][17][18][19]. Our initial approach for sample preparation was based on PPT, while it was found that liquid-liquid extraction provided a 10-fold higher sensitivity for the majority of the CYP probe substrate metabolites than PPT.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the most widely employed incubation sample preparation is protein precipitation (PPT) [11][12][13][14][15][16][17][18][19]. Our initial approach for sample preparation was based on PPT, while it was found that liquid-liquid extraction provided a 10-fold higher sensitivity for the majority of the CYP probe substrate metabolites than PPT.…”
Section: Sample Preparationmentioning
confidence: 99%
“…At present, numerous high-throughput approaches using fluorogenic substrates to measure CYP activities have been described [8,9], as well as substrate "cocktail" experiments that simultaneously measure more than one CYP activity [10][11][12][13][14][15][16][17][18]. Recently Kim et al [19] described a high-throughput method that allowed the simultaneous evaluation of the metabolic activities of nine major human CYP isoforms (i.e., CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP2E1, and CYP3A4) on their well-known specific probe substrates using human hepatic microsomes.…”
Section: Introductionmentioning
confidence: 99%
“…Upon the development of a substrate cocktail biological incubation assay there was a need for a cocktail analytical assay with appropriate throughput and sensitivity to determine a test compound's CYP450 inhibitory potential. Several LC-MS/MS-based cocktail analytical assays have been reported in the literature [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. However, many of these methods suffer from limitations such as use of recombinant CYPs, S-mephenytoin 4 -Hydroxymephenytoin CYP1A2 Tacrine 1 -Hydroxytacrine clinically irrelevant probe substrates, intensive sample preparation, use of sample preparation HPLC columns, longer run times and higher protein (HLM) content in biological incubations that provides higher substrate turnover; however, could result in nonspecific binding.…”
Section: Introductionmentioning
confidence: 99%
“…Polarity switching [2] is an approach to monitor positive and negative ions alternatively by a mass spectrometer. It is utilized with liquid-chromatographic systems to identify protein modifications [3,4], metabolites [5], and environmental hazards [6], but the instrument performance declines due to duty cycle problems, and the few seconds required for signal recovery after every such switch.The best strategy to obtain positive and negative mass spectra is to employ contemporaneous dual-polarity (DP) ion detection [7,8]. The only DP ionization approach involving liquid samples is the field-induced droplet ionization (FIDI) [9], in which positive and negative liquid jets are produced from falling droplets within a strong d.c. electric field.…”
mentioning
confidence: 99%
“…Polarity switching [2] is an approach to monitor positive and negative ions alternatively by a mass spectrometer. It is utilized with liquid-chromatographic systems to identify protein modifications [3,4], metabolites [5], and environmental hazards [6], but the instrument performance declines due to duty cycle problems, and the few seconds required for signal recovery after every such switch.…”
mentioning
confidence: 99%